2013
DOI: 10.1186/1471-2105-14-37
|View full text |Cite
|
Sign up to set email alerts
|

A novel application of motion analysis for detecting stress responses in embryos at different stages of development

Abstract: BackgroundMotion analysis is one of the tools available to biologists to extract biologically relevant information from image datasets and has been applied to a diverse range of organisms. The application of motion analysis during early development presents a challenge, as embryos often exhibit complex, subtle and diverse movement patterns. A method of motion analysis able to holistically quantify complex embryonic movements could be a powerful tool for fields such as toxicology and developmental biology to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…, 96 well plates) development for individual embryos of model ( D. rerio , X. laevis ) and emerging-model organisms ( R. balthica ) provides an excellent avenue to replicate and examine changes in the timing of developmental events in response to physiological stress ( e.g. , temperature or oxygen level changes) (Tills et al, 2013a). These types of data allow for more explicit links to be generated between heterochrony and heterokairy that to date are, unfortunately, largely treated as separate phenomena in the literature (Spicer and Rundle, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 96 well plates) development for individual embryos of model ( D. rerio , X. laevis ) and emerging-model organisms ( R. balthica ) provides an excellent avenue to replicate and examine changes in the timing of developmental events in response to physiological stress ( e.g. , temperature or oxygen level changes) (Tills et al, 2013a). These types of data allow for more explicit links to be generated between heterochrony and heterokairy that to date are, unfortunately, largely treated as separate phenomena in the literature (Spicer and Rundle, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Testing models for the importance of heterokairy is difficult for such species, given the limitations of working with preserved specimens or making observations from live embryos within opaque eggs. Recent advances in bio-imaging technology, however, allow the simultaneous in vivo observation and videoing of multiple, individual embryos, including analytical techniques that can be used to quantify physiological responses to stress in species such as R. balthica , Danio rerio and Xenopus laevis (Tills et al, 2013a). Video footage at high temporal and spatial resolution enables an integrative approach whereby physiological, behavioral and morphological traits and their time of onset and offset can be measured.…”
Section: Evolutionary Importance Of Variation In the Timing Of Devmentioning
confidence: 99%
“…Throughout the experiment, all wells were observed daily using a custom‐built bio‐imaging system for aquatic animals (Tills et al. ). Polychaetes were fed daily ad libitum on minced spinach (Massamba‐N'Siala et al.…”
Section: Methodsmentioning
confidence: 99%
“…This approach allowed us to extract important features such as buccal pumping rates and locomotor activity time. The incorporation of holistic spectral analysis of the motion analysis signals [45] could enable the automatic detection of many more movement parameters such as tail beat frequencies or temporal patterns of movements. By using tracking and motion analysis, we analyzed basal activity of tadpoles and found that tadpoles in 24-well plates are mainly immobile while performing buccal pumping at variable frequency.…”
Section: Discussionmentioning
confidence: 99%